Lack of strong association of Chlamydia pneumoniae and atherosclerosis in a Jordanian population - Hesham M Al-Younes; Mahmoud A Abu Abeeleh; Basem M Jaber (Journal of Infection in Developing Countries)
Introduction: The correlation of Chlamydia pneumoniae to coronary artery disease (CAD) in Jordan was investigated in this study. Methodology: Totals of 361 atherosclerotic patients and 392 apparently healthy controls of both sexes were enrolled. C. pneumoniae-specific IgG antibodies were measured by the microimmunofluorescence assay (MIF). The presence of the bacterial DNA in the blood by polymerase chain reaction (PCR) was also tested. Results: The overall IgG seroprevalence, estimated at a titer of 1/16, was insignificantly higher in patients (75.9%) than in controls (71.7%). About 59.3% of patients demonstrated seropositivity at titers ≤ 1/256, which are suggestive of chronic or presumed past infection, whereas 54.1% of controls were seropositive at these titers (p > 0.05). Analysis of gender-specific seroprevalences revealed no obvious relation between C. pneumoniae and atherosclerosis in males (78.9% and 77.9% in atherosclerotic and control males, respectively; p > 0.05). However, a significantly elevated seropositivity was detected in atherosclerotic females (71.7%) compared with control females (64.2%). On the other hand, the PCR-based detection of C. pneumoniae DNA failed to correlate the bacterium to atherosclerosis. Conclusions: We were unable to show a strong association between C. pneumoniae and CAD, potentially because of the presence of high seroprevalence of C. pneumoniae antibodies and the unreliability of the whole blood-based nested PCR technique used.